MENINGKATKAN KONSEP DIRI POSITIF DALAM BELAJAR DENGAN MENGGUNAKAN TEKNIK ROLE PLAYING - Asti Haryati; Yusmansyah Yusmansyah; Diah Utaminingsih (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of the research was to know the increasing of positive self-concept in learning by using role-playing techniques. The problem of this research was  the low of student’s positive self-concept in learning. The problem was "can positive self-concept increased in student learning by using role playing to the student’s class XI at SMA N 1 Natar?”. The research method used in this method quasi-experimental design with one group pretest-posttest. The research subjects were of six students with have a low self-concept in learning. Data collecting techniques using self-concept scale.The research results showed that positive self-concept in learning can be increased using role-playing techniques, it proved from the data analysis result that using Wilcoxon, from pre-test and post-test result acquired Zoutput= -2.201 and Ztabel 0.05 = 0. ZoutputZtabel. Thereby, Ha accepted, it means positive self-concept student’s class XI at SMA N 1 Natar South Lampung regency in the academic year 2012/2013 can be increased by using role-playing techniques.The conclusion is that there is an increase in positive self-concept in learning after being given role playing technique to the students class XI at SMA N 1 Natar South Lampung regency in academic year 2012/2013. The suggestion that given is (1) Students should attend the counseling service if you have difficulty in improving positive self-concept in learning, (2) to the teacher, should be able to maximize the provision of guidance and counseling services to students in schools and the use of role playing techniques to help students increase students' positive self-concept, and (3) to researchers, to conduct research on positive self-concept and role playing with a different subject.Kata Kunci :belajar,konsep diri positif,teknik role playing